2016
DOI: 10.21617/jprm.2016.0101.3
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Satisfaction with Outpatient Pharmacy Services at the University Teaching Hospital and Ndola Central Hospital in Zambia

Abstract: Background: Hospital pharmacy services offered at tertiary public hospitals in Zambia have yet to be evaluated from the perspective of the patients they serve. Main Objective: To determine patients' satisfaction with outpatient pharmacy services provided at University Teaching Hospital (UTH) and Ndola Central Hospital (NCH) in Zambia. Design: Cross-sectional descriptive study Setting: University Teaching Hospital and Ndola Central Hospital Participants: Randomly selected patients (N=150) (38% male, 62% female)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
5
1
Order By: Relevance
“…In contrast to the present study, different studies showed that age, gender, marital status, level of education were associated with clients’ satisfaction [ 15 , 17 , 22 ]. The difference might be in part due to variation in study period, and sample size of the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the present study, different studies showed that age, gender, marital status, level of education were associated with clients’ satisfaction [ 15 , 17 , 22 ]. The difference might be in part due to variation in study period, and sample size of the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…To consistently optimize satisfaction of patients for pharmacy services, it is indispensable to identify factors which could strongly predict its aspect of dissatisfaction at different cohorts of population. Published data have described levels of patient satisfaction in terms of whether or not a given healthcare service is meeting the expectations and desires of patients it serves but not exhaustively identify key areas of quality improvement in the healthcare facility ( Kalungia and Kamanga, 2016 ). Aspects such as persistent shortages or stock-outs of commonly prescribed drugs, long waiting times, and lack of privacy during medication counseling were highlighted as key areas for improvement of hospital pharmacy services ( USAID/SIAPS, 2014 ; Kalungia and Kamanga, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacy education has evolved in a bid to meet the rapidly changing demands of healthcare globally (Ifunanya, 2016). While the number of qualified pharmacists has increased significantly in the last ten years, the quality of pharmaceutical care service is an area which still requires improvement (Kalungia & Kamanga, 2016). This is due to an inadequate policy framework that promotes the expanded responsibility of pharmacists in the provision of comprehensive patient care (Kalungia et al, 2019).…”
Section: Competency and Future Directionmentioning
confidence: 99%